Strength reserve assessment on pitting-corroded jacket offshore platforms based on the modified generalized constitutive model. (December 2021) - Yang, Yang; Xu, Tianyu; Guo, Junli; He, Zheng; Ma, Houbiao
Abstract: The resulting localized stress concentration of the pitting corrosion causes a significant degradation in the mechanical performance and ultimate load-bearing capacity of steel jacket offshore platforms. Conventionally, the pitting-induced damage is usually treated as an equivalent section loss of a uniform corrosion case in which the local feature of corrosion pits cannot be properly reflected. Moreover, the observed variations of the macroscopic mechanical parameters with respect to the volume loss rate (VLR ) are used to put forward a modified generalized constitutive model (MGCM) for the pitting-corroded steel, which can be applied for both the pitting corroded steel and intact steel, based on the uniaxial tension test conducted on the pitting-corroded specimens with different degrees of pitting damage. The MGCM, which exhibit analytical accuracy, is then combined with the fiber model in assessing the strength reserve, in terms of reserve strength ratio ( RSR ), of steel jacket offshore platforms with different degrees of pitting corrosion damage. Moreover, a comparison is also conducted on platforms with equivalent uniform corrosion degrees. The assessment results show that the structural performance of pitting-corroded steel jacket offshore platforms can be rationally simulated as the effect of the pitting corrosion, which is addressed in the MGCM. The overestimate, which resulted from not considering the local characteristics of pitting corrosion in structures, can be avoided. Furthermore, the effect of the pitting corrosion on the RSR of jacket offshore platforms can be easily quantified using the VLR -based variable in the MGCM, the loading bearing capacity, and other mechanical performance indexes. Highlights: The resulting localized stress concentration of the pitting corrosion causes a significant degradation. The variations of the macroscopic mechanical parameters are used to put forward a modified generalized constitutive model for the pitting-corroded steel. The effect of the pitting corrosion on the RSR of jacket offshore platforms can be easily quantified using MGCM.